Effect of Tannin from Acacia Nilotica Pods on in vitro and in sacco Nutrient Degradability and Rumen Fermentation Pattern - Lata, Manju; Rai, S N; Sharma, Vijay Kumar; Jha, Pankaj; Jain, Pankaj; Kumar, Muneendra (Indian Journal of Dairy Science, 2012)
The study was carried out on Acacia nilotica extracted tannins on in vitro, in sacco nutrient degradability and rumen fermentation pattern.The results revealed that different extraction processes tried for tannin recovery was comparatively higher in methanol and cold water as compared to others. Two levels of tannins of pure tannic acid, extracted tannin through cold water process and babul pods were compared with different substrates such as GNC alone, concentrate mixture and TMR using 50:50 of roughage and concentrate. The in vitro nutrient digestibility (IVDMD and IVOMD) and rumen fermentation (NH3 and CH4) were reduced in tannin supplemented groups as compared to control (without tannin). However, total gas production was found higher in treated groups over control. In Sacco effective degradability of TMR was decreased in both pure tannic acid and extracted tannin powder where as babul pods did not alter the degradability.